2006
DOI: 10.1080/13607860500307530
|View full text |Cite
|
Sign up to set email alerts
|

‘It's like a revolving door syndrome’: Professional perspectives on models of access to services for people with early-stage dementia

Abstract: As the need for services for people with dementia grows, and the benefits of early intervention become clear, it has become important to understand what factors may improve access to services for people with early-stage dementia. There are a number of models of service access, and these emphasise different areas, whether individual factors, relationships, or social context. The relevance of these models to variations in service access for people with early-stage dementia, and how well they relate to profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…Similar to Pratt et al [57], we found that increasing access to services involves considering the wider social context of caregivers and their relationships with, among persons with dementia, other caregivers and professionals in order to more meaningfully understand issues of access. One model that takes social context into account is the integrated, continuing care model as proposed by Forbes and Neufeld [58].…”
Section: Discussionsupporting
confidence: 65%
“…Similar to Pratt et al [57], we found that increasing access to services involves considering the wider social context of caregivers and their relationships with, among persons with dementia, other caregivers and professionals in order to more meaningfully understand issues of access. One model that takes social context into account is the integrated, continuing care model as proposed by Forbes and Neufeld [58].…”
Section: Discussionsupporting
confidence: 65%
“…Connecting PWD and care partners with home and community services early in the course of illness can facilitate access to appropriate services when required, and in a timely and efficient manner; this has the potential to prevent crisis events resulting from unrecognized care needs and inadequate support. This strategy addresses many of the barriers to services for PWD, particularly as related to awareness of available services, system navigation, and the need for PWD and care partners to repeatedly retell their stories and “push” for services. The PCCMC–H&CC partnership provides a significant opportunity to support team case management, where the unique knowledge and expertise of each interprofessional team member contributes to the coordination of dementia care …”
Section: Themes Generated By Analysis Of Interview Transcripts With Imentioning
confidence: 99%
“…1,2 Despite the availability of many communitybased services to support PWD living at home, these services are often not accessed until late in the disease process or when a crisis situation arises. 3,4 Barriers to accessing community services include limited knowledge of available services, lack of system navigation support, duplicative assessments and long wait lists; 5,6 many care partners are left feeling that they have to "fight" to access services. 6 The Primary Care Collaborative Memory Clinics (PCCMC) model of dementia care aims to improve the quality of dementia care by providing person-centered care that includes meeting the needs of care partners.…”
Section: Dear Editormentioning
confidence: 99%
“…Navigating the different systems of care is particularly difficult for this population, not least because they receive advice and support from health and social care and increasingly third-sector providers. 39 Previous research on continuity has identified a need to prioritise the needs of vulnerable people who are unable to negotiate their own continuity as they wish. 40 Processes of care may be further complicated for PLWD who have other comorbid health conditions.…”
Section: Continuity Of Carementioning
confidence: 99%